Analisa Komparatif Perencanaan Perkerasan Lentur Jalan Kabupaten Antara Manual Desain Perkerasan Jalan (MDP) 2024 dan Metode Analisa Komponen - Pratama, Nicko; Putri, Elsa Eka; Purnawan , Purnawan (Syntax Corporation, 2025)
In the era of rapid infrastructure development in Indonesia, the efficiency of road planning has become crucial in optimizing the utilization of regional budgets. This study compares two flexible pavement design methods: the newly introduced Pavement Design Manual (MDP) 2024 and the long-established Component Analysis Method, focusing on district roads in Lunang Subdistrict. The results of this study demonstrate that MDP 2024 not only produces a pavement design that is 4% thinner but also potentially reduces the budget by up to 9%. Detailed analysis reveals that the estimated cost required for a 3.1 km road pavement using the Component Analysis Method is IDR 9,162,006,089, while MDP 2024 requires only IDR 8,277,185,847, resulting in a substantial saving of IDR 884,820,242. These findings present significant opportunities for local governments to reallocate funds to other critical sectors without compromising infrastructure quality. Beyond a mere technical comparison, this research offers a blueprint for transformation in regional development planning, promising long-term positive impacts on the local economy and quality of life. With broad potential for application throughout Indonesia, this study is relevant not only to planners and engineers but also to policymakers and the general public concerned with sustainable development and public budget efficiency.